Identification Polymorphism of Melanocortin 1 Reseptor (MC1R) Gene in Bali Cattle by using PCR-RFLP Method - Arnold , Ch Tabun; Sumadi, Sumadi; Diah s , Volkandari; Tety, Hartatik (2013)
The aim of the research was to identify the MC1R gene of Bali cattle in Kupang regency. Total samples which used in this research consist of 43 cows (17 Red-brown/sorrel, 18 black, 8 white) and three bulls. The polymorphism of Melanocortin 1 Reseptor (MC1R) Gene was identified using PCR-RFLP method. The PCR product of MC1R-gene shows 296 base pair band in 1% agarose gel electrophoresis. The volume 3 µl PCR product was digested by 1U MspI-restriction enzyme. The results indicate two type of restriction fragment, EE type consist of two bands (169 and 36 bp) and Ee type consist of three bands (296, 169, and 136 bp). The allele frequencies of MC1R gene were E = 0,99 and e= 0,01. One of 46 samples has Ee genotype. Even base on allele frequencies show that MC1R genes were monomorphic, it may has differrent results due to the number of samples. Polymorphism of MC1R gene could be used as coat color markers of Bali Cattle in Kupang population. Since the genetic variation of Bali cattle occur base on coat colour, and the preference of the society in Kupang to keep those cattle, so it is needed to conserve the diversity to promote the development of sustainable for Bali cattle.